Finding your own north star eaudiobook Claiming the life you were meant to live. - Beck, Martha (Tantor Media, 2016)
"The North Star—Stella Polaris—is a fixed point that can always be used to figure out which way you're headed. Explorers and mariners can depend on Polaris when there are no other landmarks in sight. The same relationship exists between you and your right life, the ultimate realization of your potential for happiness. I believe that a knowledge of that perfect life sits inside you just as the North Star sits in its unaltering spot. You may think you're utterly lost, but brush away the leaves, wait for the clouds to clear, and you'll see your destiny shining as brightly as ever; the fixed point in the constantly changing constellations of your life." —Martha Beck As the creator of Life Designs, Inc., Martha Beck has helped hundreds of clients find their own North Star and figure out how to fulfill their potential and create joyful lives through her lectures, seminars, and one-on-one counseling. In this book, she shares her step-by-step program that will guide you to fulfill your own potential.